ANATOMI PRAKTIK PETTY CORRUPTION DI LINGKUNGAN SEKOLAH: DEKONSTRUKSI NORMALISASI KECURANGAN MELALUI PENDIDIKAN ANTIKORUPSI - lutfil Hakim; Cecep Darmawan; Ratna Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Macro level corruption practices are often rooted in the tolerance of normalized micro-scale deviations (petty corruption) during adolescence. This study aims to identify the forms, analyze the causal factors, map the implications, and formulate mitigation strategies for petty corruption through Anti-Corruption Education. Employing a qualitative approach with an embedded single case study design, this research was conducted at SMP Negeri 29 Bandung. Preliminary data from 88 respondents indicated a high prevalence of infractions, dominated by delayed assignment submissions (10.2%), tardiness (9.0%), and financial deceit (7.9%). Subsequent data collection was conducted through in-depth interviews, participant observation, and document analysis. The data were analyzed using the analytical frameworks of the Fraud Triangle Theory and the Broken Windows Theory. The findings indicate that rationalization and peer pressure serve as the primary driving forces behind petty corruption. Pedagogical interventions through the exemplary conduct of Pancasila and Civic Education (PPKn) teachers, coupled with the habituation of a climate of integrity, have proven essential in deconstructing corrupt mentalities and restoring the civic disposition of the students